Development of a new tandem mass spectrometry method for urine and amniotic fluid screening of oligosaccharidoses. (15th May 2017) - Piraud, Monique; Pettazzoni, Magali; Menegaut, Louise; Caillaud, Catherine; Nadjar, Yann; Vianey‐Saban, Christine; Froissart, Roseline
Abstract : Rationale: The first step in the diagnosis of oligosaccharidoses is to evidence abnormal oligosaccharides excreted in urine, usually performed by the poorly sensitive but efficient thin layer chromatography (TLC) method. Developing a tandem mass spectrometry (MS/MS) technique could be of great interest to replace TLC. Methods: Abnormal underivatized oligosaccharides have been recently studied using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry, allowing the unambiguous identification of oligosaccharidoses. Based on this previous work, we developed an advantageous and efficient liquid chromatography (LC)/MS/MS method using a more common triple quadrupole tandem mass spectrometer for oligosaccharides analysis. Results: Oligosaccharidoses ( n = 97) and control ( n = 240) urine samples were analysed. A specific pattern was obtained for each oligosaccharidosis using this method. In urine, it allows not only the identification of all the oligosaccharidoses previously identified by TLC (fucosidosis, alphamannosidosis, aspartylglucosaminuria, GM1 gangliosidosis, sialidosis, galactosialidosis and Schindler disease), but also extends the field of diagnosis to mucolipidosis type II, Sandhoff disease, and β ‐mannosidosis. The same technique was applied to 16 amniotic fluid supernatants from oligosaccharidosis‐affected foetuses ( n = 16) compared with 37 unaffected. All the affected foetuses could be clearly identified: sialidosis ( n = 3), galactosialidosis ( n = 4), aspartylglucosaminuria ( n = 1), mucolipidosis type II ( n = 4) or GM1 gangliosidosis ( n = 4). This technique can be applied to early prenatal diagnosis as well as to the oligosaccharidosis screening in the case of non‐immune hydrops fetalis . Conclusions: The method is quick and easy to run, with an LC analysis time of 13 min per sample. The quantitative validation could not be obtained in the absence of a specific standard and of a labelled internal standard for each compound. Even if this LC/MS/MS method is only qualitative, it is very specific and much more sensitive than TLC. It allows the urinary screening of oligosaccharidoses, even mild or late‐onset forms, and the screening of antenatal forms in amniotic fluid. Copyright © 2017 John Wiley & Sons, Ltd.